Parents’ Social Value and Prestige in the Choice of Schools for Children - Chaulagai, Sangam (International Research Journal of MMC, 2024)
Choice of schools is a significant factor that may affect children’s future careers. After the beginning of privatisation of school education in Nepal, parents have choices either to choose government-aided schools or private schools for their children. The purpose of this study was to explore how parents’ social value and prestige influenced the choice of schools for their children. This study analysed and interpreted data from a Marxist concept of sign exchange value employing a qualitative research design. The data were collected through semi-structured interviews from two government-aided and two private schools. Ten parents and four headteachers of those schools were the participants of this study. The research found that social value and prestige of parents are significant factors in the choice of schools. Many of the parents desired to admit their children to expensive private schools rather than in government-aided schools to maintain their social status.